Making men : sophists and self-presentation in ancient Rome - Gleason, Maud W., 1954- (Princeton University Press, 1995)
The careers of two popular second-century rhetorical virtuosos offer Maud Gleason fascinating insights into the ways ancient Romans constructed masculinity during a time marked by anxiety over manly deportment. Declamation was an exhilarating art form for the Greeks and bilingual Romans of the Second Sophistic movement, and its best practitioners would travel the empire performing in front of enraptured audiences. The mastery of rhetoric marked the transition to manhood for all aristocratic citizens and remained crucial to a man's social standing. In treating rhetoric as a process of self-presentation in a face-to-face society, Gleason analyzes the deportment and writings of the two Sophists - Favorinus, a eunuch, and Polemo, a man who met conventional gender expectations - to suggest the ways character and gender were perceived.